The Cost of Compliance With Product Standards For Firms In Developing Countries : An Econometric Study - Maskus, Keith E. 1954- (The World Bank, 2005)
Standards and technical regulations exist to protect consumer safety or to achieve other goals, such as ensuring the interoperability of telecommunications systems, for example. Standards and technical regulations can, however, raise substantially both start-up and production costs for firms. Maskus, Otsuki, and Wilson develop econometric models to provide the first estimates of the incremental production costs for firms in developing nations in conforming to standards imposed by major importing countries. They use firm-level data generated from 16 developing countries in the World Bank Technical Barriers to Trade (TBT) Survey Database. Their findings indicate that standards do increase short-run production costs by requiring additional inputs of labor and capital. A 1 percent increase in investment to meet compliance costs in importing countries raises variable production costs by between 0.06 and 0.13 percent, a statistically significant increase. The authors also find that the fixed costs of compliance are nontrivial-approximately